Chinese and Western Comedy – an Introduction into Cross-Cultural Humour Research between Taiwan, China and the West - Konrad Piwowarczyk (Nowa Polityka Wschodnia, 2019)
The use of humour, both proper and improper, can influence the outcomes of meetings and shape entire relationships. Hence, although often trivial in nature, humour can play a significant role in human lives and deserves to be taken seriously. The same is true when it comes to the analysis of humour across cultures. In today’s increasingly globalized world, where people from various cultures interact on an almost daily basis it is important to understand the other persons culture, including their sense of humour. Consequently, this article provides a basic overview of humour of the world’s two biggest and most prominent cultures: the English speaking West and the Sinitic world. There is no doubt Chinese and Western humour differ in history and contemporary structure, therefore this article presents the various forms of comedic expression found in both cultures, but also provides basic explanations as to the reasons behind these differences.